Employment Of War Invalids In Uzbekistan During World War II: Historical Analysis (Eurasian Journal of Engineering and Technology, 2026)
This article investigates the policies and practical measures adopted by the Soviet state to integrate war invalids into the labor force within Uzbekistan during the Second World War. Drawing on archival documents, legislative acts, and statistical data, the study examines the scope of employment challenges faced by returning disabled veterans and the administrative responses developed at both central and regional levels. The article demonstrates that, despite formal commitments to protect the labor rights of invalids, significant bureaucratic and systemic obstacles hindered the full realization of these policies.